PENGARUH GOOD CORPORATE GOVERNANCE, PERTUMBUHAN PERUSAHAAN, DAN KINERJA LINGKUNGAN TERHADAP CORPORATE SOCIAL RESPONSIBILITY - Yaumil Khoiriyah; Refysha Syafilia Wirawan (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2021)
The purpose of this study was to obtain empirical evidence regarding the effect of Good Corporate Governance, company growth, and environment performance towards corporate social responsibility of registered manufacturing companies on the Indonesia Stock Exchange in 2016- 2018. The population of this study was the registered manufacturing companies on the Indonesia Stock Exchange (BEI) in 2016-2018. The technique of selecting samples was purposive sampling. Therefore, the sample was 38 manufacturing companies. The method of analysis uses descriptive statistical analysis methods. The results of this study proved that managerial ownership, institutional ownership, foreign ownership, and company growth did not affect on corporate social responsibility. Furthermore, the Audit Committee, board of commissioners, and environment performance affected on corporate social responsibility